Digital Social Networks and Univerity Youth: An Emergent Topic in Educational Research - Domínguez Pozos, Fernando de Jesús (2016)
In this article, the lines of research that have permeated the way to analyze the relationship between Mexican university students and online social networks in the period 2010-2015 are described. The findings show centralization in research on the topic of digital social networks because most research is carried out in the context of Mexico City; a second finding is the evolution of the social networks that have been favored among university students in such a short span of five years, beginning with networks such as Hi-5, Myspace to existing social networks like Facebook, WhatsApp and Instagram, which speaks of a constant transformation of the networks that are positioned in youth’s imaginary. It is considered a first approach that identified progress and challenges in this emergent topic in educational research, thereby making appear a period of transition from descriptive studies to studies of the interpretive sort, which lead us to understand the phenomenon of digital social networks and their interaction with university youths.